(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2008)
ABSTRACT Contradicting the notion that The Day of the Jackal is nothing but a skillfully produced and ultimately conventional film, this article argues that it gains relevance by presenting formal and thematic features that make demands on the viewer in terms of narration which are not usually made by the classical Hollywood film, a category it can be inserted in. This unusual narrative structure favors an identification of the viewer with the ideology that it implicitly supports. Key words: classical Hollywood film; role of the viewer; identification